Reinterpretation Reinterpretation of Surah At Taubah Verse 29 Against Acts of Terrorism Using Ma'na-Cum-Maghza Approach in Efforts to Prevent Islamophobia - Irbah, Zukhruful (Kontemplasi: Jurnal Ilmu-Ilmu Ushuluddin, 2023)
Abstract: Islamophobia is a phenomenon of fear and threat to Islam. On January 21 2023, an incident occurred when the Koran was burned in Sweden. Islamophobia in this case is triggered by historical trauma due to what some members of extreme Islamic groups have done. This group tends to understand and adhere to the ideology of confrontation that the word "war" in the letter At Taubah verse 29 is only physical warfare against enemies and against people who have different opinions through acts of terror. The formulation of the research problem is how to interpret Surah At Taubah verse 29 using the Ma'na Cum Maghza approach and how to contextualize this interpretation towards acts of terrorism as an effort to ward off Islamophobia? Researchers use this type of library research. The results of research using the Ma'na Cum Maghza approach are that all the behavior and attitudes of Muslims shown are back to the behavior and attitudes of non-Muslims towards Muslims. Muslims are only allowed to attack if they attack Muslims first. In the contextual realm, this verse shows that Islam is a friendly religion and not a cause of chaos, unlike what is said by Islamophobic people. In the current era, there are many various behaviors that are not in accordance with the teachings of the Islamic religion. However, that doesn't mean this has to be immediately shared and fought.